Nigeria CAADP bienniel review brief: Africa agriculture scorecard performance and lessons - Federal Ministry of Agriculture and Rural Development; Regional Strategic Analysis and Knowledge Support System (International Food Policy Research Institute, 2019)
As part of the commitment to mutual accountability for action and results, the Heads of State agreed and encouraged member countries to conduct reviews of the performance of their agriculture sectors every 2 years (Biennial Reviews; BR). The aim of the reviews is to ensure continuous tracking, monitoring, and reporting on progress, based on the Malabo commitments. The BR compares a countries’ 2016 performance with where they need to be in order to achieve the 2025 Malabo targets—in other words, the report assesses whether countries are on track to meet the targets.